Ownership and Participation: Toward a Development Paradigm based on Beneficiary-led Aid. Issue 3 (September 2014) - Flint, Adrian; Natrup, Christian Meyer zu
This article makes the case for a development paradigm shaped and determined by the people affected directly by aid and assistance programs: in essence, it is a call for beneficiary-led aid (BLA). Over the past two decades, input from beneficiaries has become increasingly important in the design of development programs. At the same time, the donor model remains one that is top-down, agenda driven, and expert led. Similarly, the use of information and communications technology (ICT) by donors in the interests of facilitating closer engagement with beneficiaries has been ongoing for over a decade. However, while the ICT4D (ICT for development) model has generated a great deal of enthusiasm within the donor community, the approach has yet to generate a discernible paradigm shift where the provision of aid and assistance is concerned. Taking inspiration from initiatives both within and outwith the field of development, we explore the extent to which ICT can indeed offer a route through which to revolutionize the meaning of "participation" in an aid context, for beneficiaries, donors, and development experts alike.